Measurement Characterization of Band‐Pass NGD Time Domain of a 101O‐Topology Passive Circuit. Issue 4 (5th April 2022) - Zhou, Xiang; Gu, Zhaoyuan; Ji, Qizheng; Hu, Xiaofeng; Vauché, Rémy; Haddad, Fayrouz; Murad, Nour Mohammad; Frnda, Jaroslav; Rahajandraibe, Wenceslas; Wan, Fayu; Ravelo, Blaise
Abstract: The negative group delay (NGD) is one of less familiar electronic functions. So far, the time domain (TD) experimentation of NGD circuits remains a challenging task. This paper investigates an innovative TD measurement of a band‐pass (BP) NGD passive circuit. The topology of the considered BP NGD distributed circuit constituted by transmission line structure having a 101O‐geometrical shape is introduced. After the design description of the 101O‐structure, the NGD response illustrates from simulation and measurement based on S‐parameters. The NGD center frequency, bandwidth, and value are approximately 3.6 GHz, 33 MHz, and −4.9 ns, respectively. The TD measurement experimentation is based on the sine carrier‐modulated microwave signal generation with 50‐ns duration. The 101O‐NGD circuit input and output signals are plotted with innovative synchronization. It was shown from the TD‐simulated and measured results that the BP NGD effect induces an output envelope about 4.2 ns advanced of the test signal input. Key Points: This study investigates a band‐pass (BP) negative group delay (NGD) The topology of the considered BP NGD distributed circuit is constituted by transmission line structure having a 101O‐geometrical shape The circuit behaves as a BP NGD function with center frequency of about 3.6 GHz and NGD value of about −3.6 ns